1988
DOI: 10.1246/bcsj.61.393
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal and Molecular Structure of Scandium(III), Yttrium(III), and Some Lanthanoid(III) p-Toluenesulfonates, [Sc(C7H7SO3)2(H2O)4](C7H7SO3)·2H2O and [M(C7H7SO3)2(H2O)6](C7H7SO3)·3H2O (M=Y, Sm, Gd, Dy, Ho, Er, Yb); and Yttrium(III) and Dysprosium(III) 2-Naphthalenesulfonates, [M(C10H7SO3)2(H2O)6](C10H7SO3)·3H2O (M=Y, Dy)

Abstract: Scandium(III) p-toluenesulfonate hexahydrate, as well as the isomorphous yttrium(III) and six lanthanoid(III) (Sm, Gd, Dy, Ho, Er, and Yb) p-toluenesulfonate enneahydrates, were synthesized and their structures were determined by the single-crystal X-ray diffraction technique. The scandium salt was monoclinic with the space group P21⁄a, Z=4 (the cell constants were a=23.672(16), b=15.792(6), c=7.7543(12) Å, β=92.86(3)°, and the final R value was 0.059). The central metal atom is hexa-coordinated, being in an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…(1967) Introduction. p-Toluenesulfonate salts have been extensively utilized as leaving groups in organic syntheses and as anions in many inorganic reactions (Ohki, Suzuki, Takeuchi & Ouchi, 1988;Bernhard, Burgi, Hauser, Lehmann & Ludi, 1982). The isolation of the title complex was a result of our efforts directed to the synthesis and modification of crown ethers with improved heavy-metal extraction properties.…”
mentioning
confidence: 99%
“…(1967) Introduction. p-Toluenesulfonate salts have been extensively utilized as leaving groups in organic syntheses and as anions in many inorganic reactions (Ohki, Suzuki, Takeuchi & Ouchi, 1988;Bernhard, Burgi, Hauser, Lehmann & Ludi, 1982). The isolation of the title complex was a result of our efforts directed to the synthesis and modification of crown ethers with improved heavy-metal extraction properties.…”
mentioning
confidence: 99%
“…[22] Since the coordination number of the trivalent lanthanide ion is commonly eight or nine, it has been suggested that the coordination mode of the sulfonate anions changes upon removal of the hydrated water molecules from the crystal, so that they act as multidentate ligands forming more metal-oxygen bonds in order to replace the removed water oxygen atoms in the first coordination sphere of the lanthanide(iii) ion. The elemental analysis results of lanthanide(iii) tosylate catalysts (see Experimental Section) indicated that some water of crystallization is lost upon drying of the crystalline solid at 50°C in vacuo, but that the complexes still contain one to three molecules of water.…”
Section: Synthesis and Characterization Of The Catalystsmentioning
confidence: 99%
“…[22,26] For example, in the La(TOS) 3 ·9 H 2 O complex, nine water molecules occupy the first coordination sphere and the tosylate counterions are merely spectator ions located in the second coordination sphere. [26] In contrast, the structure of Yb(TOS) 3 is markedly different: the coordination environment around the ytterbium(iii) is occupied by two oxygen atoms from the sulfonate group of TOS and six oxygen atoms from water molecules.…”
Section: Postulated Mechanism For the Yb(tos) 3 -Catalyzed Acylationmentioning
confidence: 99%
“…55°C. [16] As the coordination number of the lanthanides is always high (commonly 8 or 9), it has been proposed that upon removal of hydrated water molecules from the crystal, the sulfonate anions move and act as multidentate ligands forming more metal-oxygen bonds in place of the removed water oxygen atoms. The elemental analysis results of lanthanide() complexes with nitrosulfonic acids (Exp.…”
Section: Synthesis and Characterization Of The Catalystsmentioning
confidence: 99%
“…In contrary, the ytterbium() tosylate complex has a structure very similar to the structure of Yb(m-NBSA) 3 in which two ligands are directly bound to ytterbium(). [16] The analogy between the structures of the lanthanide() nitrobenzenesulfonate and lanthanide() tosylate complexes is not surprising, if one takes into account the similarities of the nitrobenzenesulfonate and tosylate structures and their similar pK a values.…”
Section: Role Of the Counterions In The Nitration Reactionmentioning
confidence: 99%